Penerapan Model Paikem pada Pembelajaran PAI dalam Meningkatkan Minat Belajar Siswa Kelas IV di SDN 61 Karara Kota Bima - Trimansyah, Trimansyah; Rosmiati, Rosmiati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study is todetermine the application of the PAIKEM learning model to PAI learning as a learning model that can increase student interest in learning, the type used in this study is a qualitatve research type with a descriptve approach, data collection using an interview model, observation and documentation. With research analysis begins with data collection, data reduction, data display and conclusion. The resultsof the teaching and learning ocess in PAI subjects in elementary schools using the PAIKEM model show maximum and good results. This is marked by changes in students' attitudes, behavior and emotions, for example, before entering class they are good at bringing greetings. according to interacting with fellow students and with teachers, this is a very significant result after applying the PAIKEM model to each learning process which is seen as an increase in attitudes and changes from the previous one.